FaceIt: Supporting Reflection upon Social Anxiety Events with Lifelogging - Rennert, Kara; Karapanos, Evangelos (My University, 2013)
Many reasons prevent those with mental health problems from maintaining and maximizing effective therapy. In this paper we explore the merits of a multimodal mobile mental health intervention designed to enhance adherence and outcomes in using cognitive behavioral therapy methods for social anxiety disorder. This mobile system combines several facets of guided lifelogging to assist in meeting the challenges of completing cognitive behavioral therapy tasks and recording occurrence data helpful for treatment. FaceIt is a multi-level mobile intervention that supports recall and reflection for completing daily mood logs and exposure therapy, and also uses location, duration, and severity information to track where problems occur, how often, and their duration in order to document user progress.
Keywords: Cognitive Behavioral Therapy; Lifelog; Social anxiety